Association of maternal characteristics with latino youth health insurance disparities in the United States: a generalized structural equation modeling approach - Cinthya K. Alberto; Jessie Kemmick Pintor; Brent Langellier; Loni Philip Tabb; Ana P. Martínez-Donate; Jim P. Stimpson (BMC, 2020)
Abstract Background Disparities in access to care persist for Latino youth born in the United States (US). The association of maternal characteristics, such as maternal citizenship status and insurance coverage, on youth health insurance coverage is unclear and is important to examine given the recent sociopolitical shifts occurring in the US. Methods We analyzed pooled cross-sectional data from the 2010-2018 National Health Interview Survey to examine the association of Latina maternal citizenship status on maternal insurance coverage status and youth uninsurance among US-born Latino youth. Our study sample consisted of 15,912 US-born Latino youth (ages < 18) with linked mothers. Our outcome measures were maternal insurance coverage type and youth uninsurance and primary predictor was maternal citizenship status. Generalized structural equation modeling was used to examine the relationships between maternal characteristics (maternal citizenship, maternal insurance coverage status) and youth uninsurance. Results Overall, 7% of US-born Latino youth were uninsured. Just 6% of youth with US-born mothers were uninsured compared to almost 10% of those with noncitizen mothers. Over 18% of youth with uninsured mothers were uninsured compared to 2.2% among youth with mothers who had private insurance coverage. Compared to both US-born and naturalized citizen Latina mothers, noncitizen Latina mothers had 4.75 times the odds of reporting being uninsured. Once adjusted for predisposing, enabling, and need factors, maternal uninsurance was strongly associated with youth uninsurance and maternal citizenship was weakly associated with youth uninsurance among US-born Latino youth. Conclusion Maternal citizenship was associated with both maternal uninsurance and youth uninsurance among US-born Latino youth. Federal- and state-level health policymaking should apply a two-generational approach to ensure that mothers of children are offered affordable health insurance coverage, regardless of their citizenship status, thus reducing uninsurance among US-born Latino youth.